Spontaneous grafting of 9, 10-phenanthrenequinone on porous carbon as an active electrode material in an electrochemical capacitor in an alkaline electrolyte1. Issue 11 (21st March 2015) - Le Comte, A.; Chhin, D.; Gagnon, A.; Retoux, R.; Brousse, T.; Bélanger, D.
<x xml:space="preserve">Abstract</x> Spontaneous grafting of 9, 10-phenanthrenequinone (PQ) on Black Pearls carbon by reduction of the corresponding in situ generated diazonium cations has been successfully achieved.